2018
DOI: 10.1186/s13584-018-0240-1
|View full text |Cite
|
Sign up to set email alerts
|

Taxation of sugar sweetened beverages and unhealthy foods: a qualitative study of key opinion leaders’ views

Abstract: BackgroundFiscal policies to fight obesity such as taxation of unhealthy foods or sugar-sweetened beverages (SSBs) have gained considerable attention in recent years. Many studies modelling the impact of various magnitudes of taxes on SSB purchasing and their potential effects on various health outcomes have been published; however, legislation and implementation of such taxes have encountered many obstacles in the countries that have implemented them to date. We investigated the perceptions and views of key o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 37 publications
1
56
1
Order By: Relevance
“…Other than communicating price changes, the results also suggest that it is important to combine price increases and discounts. Subsidies alone may lead to an increase in overall calorie consumption [34] and taxes may be more accepted by the public when the tax revenue is earmarked to subsidize healthy foods [35]. Therefore, combining subsidies with taxes may be more effective than implementing just one of the two strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Other than communicating price changes, the results also suggest that it is important to combine price increases and discounts. Subsidies alone may lead to an increase in overall calorie consumption [34] and taxes may be more accepted by the public when the tax revenue is earmarked to subsidize healthy foods [35]. Therefore, combining subsidies with taxes may be more effective than implementing just one of the two strategies.…”
Section: Discussionmentioning
confidence: 99%
“…51 Israel: support for tax dependent on use for health promotion (mix of stakeholders). 52 A systematic review of the literature concluded that public acceptability was increased if the revenue was used for beneficial purposes. 53 South Africa: cynicism that the tax is for health purposes, not government revenue.…”
Section: Acceptability To Stakeholdersmentioning
confidence: 99%
“…We also advocate for a percentage of revenues to be directed towards oral health promotion. A similar call has been made by other key opinion leaders, including The British Society of Paediatric Dentistry, the British Association for the Study of Community Dentistry, and local councils in the UK.…”
Section: Revenue Is Not Being Used For Oral Healthmentioning
confidence: 83%